Ultra high-performance concrete as alternative repair method: A review - Siti Rahimah, Rosseli; Muhd Norhasri, Muhd Sidek; Hamidah, Mohd Saman; Mohd Fadzil, Arshad; Mohd Faizal, Md Jaafar; Ahmad Ruslan, Mohd Ridzuan; Putra Jaya, Ramadhansyah; Hafizah, Muhamad Azlan (Springer Nature, 2021)
This review paper discussed on the behavior of Ultra High-Performance Concrete (UHPC) in the concrete industry. Since the emergence of unique design of concrete, the needs of UHPC can contribute to alternative solutions to the High-Performance Concrete (HPC) and also normal concrete. In this review, definition, materials and techniques of producing, chemical analysis, and prediction software on previous and current works of UHPC were presented. Moreover, in this paper, the benefits of UHPC as compared to the types of concrete were also discussed. As a conclusion, UHPC needs to be implemented more in the construction nowadays. Extra strong, durable, and slimmer design of concrete structures can be an alternative to a sustainable and economic design that can last longer with less supervision.